LEGAL PROTECTION FOR VICTIMS NARCOTIC ABUSE AND ITS RULE OF LAW - Anggitha Putri Larasati; Margo Hadi Pura (Wacana Hukum, 2021)
The drug problem in Indonesia is still urgent and complex. In the past decade, this problem has become rampant. This is proven by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of cases of drug crimes with more diverse patterns and more massive syndicate networks. The Indonesian people, even the world community, in general are currently faced with a very worrying situation due to the rampant use of various types of illegal drugs. Narcotics crimes are no longer committed individually, but involve many well-organized people with a wide network and an increasingly sophisticated mode. The Narcotics Law Number 35 of 2009 was enacted to overcome this condition.